Low Temperature Crystallization for Vitamin E Concentrate Preparation from Palm Fatty Acid Distillate: Study on Solvent Type - Ahmadi, Kgs. (Fakultas Teknologi Pertanian Universitas Brawijaya, 2010)
Palm Fatti Acid Distillate (PFAD) is one source of natural vitamin E enrich with tocotrienol. Â This research aimed to aplly low temperature solvent crystallyzation in vitamin E concentrate preparation from PFAD. Â The advantage of this method is simple and low temperature use. Â The crystallized PFAD fraction was unsaponifiable fraction from saponification process. Â The elucidated factor was solvent type. Â The result showed that PFASD contained vitamin E comprised of ï¡ tocopherol and ï¡, Â ï¤, ï§ tocotrienol and the major component was fatty acids. Â The saponification process decreased free fatty acid content and increased vitamin E concentration. Â The solvent type affected the characteristic of vitamin E concentrate including the concentration of vitamin E, antioxidant activity, free fatty acids content, and yield. Â The most suitable solvent was hexane due to its non polar characteristic.Keywords: low temperature crystallization, vitamin E concentrate, palm fatty acid distillate